Serum interleukin-6 and C-reactive protein as a prognostic indicator in hepatocellular carcinoma - Jang, Jeong Won; Oh, Byong Sun; Kwon, Jung Hyun; You, Chan Ran; Chung, Kyu Won; Kay, Chul Seung; Jung, Hyun Suk (Cytokine (Philadelphia, Pa.), 2012)
► There is the presence of increased Th2-cytokine patterns in patients with HCC compared to healthy controls. ► IL-6 is an independent predictor of survival in patients with HCC treated with loco-regional therapy. ► CRP and IL-6 are linked to both tumor burden and hepatic reserve function. ► The changes in CRP levels provide a good predictive capacity of tumor response. The development of hepatocellular carcinoma (HCC) is often associated with chronic inflammation, suggesting a strong relationship between inflammation and carcinogenesis. This study evaluated the prognostic values of inflammatory and T-helper (Th) cytokines in the clinical outcome and survival of HCC. The study included 110 patients with HCC undergoing loco-regional therapy and 24 healthy controls. Five Th1/Th2 cytokines and C-reactive protein (CRP) were quantified before and after loco-regional treatment, using enzyme-linked immunosorbent assays. Levels of CRP, interleukin (IL)-4, and IL-6 were higher in patients with HCC than those in healthy subjects. Tumor characteristics, Child-Pugh class, and CRP, IL-6, and IL-10 levels were associated with HCC survival (all P<0.05). With multivariate analysis, higher IL-6 levels were identified as the independent cytokine for shorter survival (P=0.010). Higher CRP and IL-6 levels correlated well with larger tumor size, poor Child-Pugh function, and shorter survival, with a significant inter-correlation (r=0.667). On serial measurements, the association of CRP with tumor response was stronger than that of α-fetoprotein or other cytokines. IL-6 and CRP are strong inflammatory indicators predictive of outcome in patients with HCC receiving loco-regional therapy. This study suggests that inflammatory activation of the IL-6/CRP network may be a potential therapeutic target and biomarker for HCC.